Antagonizing cis- regulatory elements of a conserved flowering gene mediate developmental robustness - Amy Lanctot; Anat Hendelman; Peter Udilovich; Gina M. Robitaille; Zachary B. Lippman (Proceedings of the National Academy of Sciences, 2025)
Developmental transitions require precise temporal and spatial control of gene expression. In plants, such regulation is critical for flower formation, which involves the progressive maturation of stem cell populations within shoot meristems to floral meristems, followed by rapid sequential differentiation into floral organs. Across plant taxa, these transitions are orchestrated by the F-box transcriptional cofactor gene UNUSUAL FLORAL ORGANS ( UFO ). The conserved and pleiotropic functions of UFO offer a useful framework for investigating how evolutionary processes have shaped the intricate cis- regulation of key developmental genes. By pinpointing a conserved promoter sequence in an accessible chromatin region of the tomato ortholog of UFO , we engineered in vivo a series of cis- regulatory alleles that caused both loss- and gain-of-function floral defects. These mutant phenotypes were linked to disruptions in predicted transcription factor binding sites for known transcriptional activators and repressors. Allelic combinations revealed dosage-dependent interactions between opposing alleles, influencing the penetrance and expressivity of gain-of-function phenotypes. These phenotypic differences support that robustness in tomato flower development requires precise temporal control of UFO expression dosage. Bridging our analysis to Arabidopsis , we found that although homologous sequences to the tomato regulatory region are dispersed within the UFO promoter, they maintain similar control over floral development. However, phenotypes from disrupting these sequences differ due to the differing expression patterns of UFO . Our study underscores the complex cis- regulatory control of dynamic developmental genes and demonstrates that critical short stretches of regulatory sequences that recruit both activating and repressing machinery are conserved to maintain developmental robustness.